Konsep Pengajaran Teologi "Doktrin Allah" Menurut Perspektif Iman Kristen - Maria Agustina; Adelia Karunia; Lola Aprilia; Titus Reinhard Habakuk; Samauli (An Nafi': Multidisciplinary Science, 2025)
The doctrine of God is a central teaching in Christian theology that shapes the faith and life of believers. This study explores the nature and attributes of God as revealed in the Bible, emphasizing both His immanence and transcendence. God is presented as a personal being who is close to humanity and desires a relationship with His creation. Scriptural references such as Hosea 6:3 highlight the call for humans to know God, while Isaiah 40:18 reminds believers of God’s infinite and incomprehensible nature. The doctrine further elaborates that God is spirit, without physical form, as indicated in Luke 24:39, and is omnipresent, omniscient, and omnipotent. Jesus Christ is understood as the visible representation of the invisible God, making divine attributes accessible to humanity. The triune nature of God—Father, Son, and Holy Spirit—forms the foundation of the Trinitarian doctrine, which, though not explicitly named in the Bible, is derived from biblical revelation in both the Old and New Testaments. This study underscores that understanding God’s attributes and the doctrine of the Trinity is vital for deepening faith and guiding Christian life. It encourages believers to pursue a personal and meaningful relationship with God, reflecting His holiness, justice, and perfect love in their daily lives.